Postmortem ultrasonographic report of abdominal organs in an andean bear (Tremarctos ornatus) - Cahua U., Jacqueline (2012)
A postmortem ultrasonography study was performed in the abdominal organs of an Andean bear (Tremarctos ornatos), 28 years old and 38 kg body weight, raised in captivity. The liver showed a hypoechoic homogeneous parenchyma, with six lobes, where the caudate lobe was extended to the last right intercostal and the left medial lobe completely covered the stomach body. The gallbladder, in a pear-shape, was 76.9 mm long, 27 mm thick, and had a 2.8 mm hyperechoic wall and anechoic content. The spleen was located in the left hypochondria, cranial to the kidney; showing homogeneous parenchyma, coarse-grained, and echogenicity slightly increased compared to the liver. The stomach was located caudal to the visceral surface of liver, and showed a division of four segments in relation to the thickness of the wall. The duodenum was located on the right flank (8.2 mm thickness, 18.5 mm diameter). The walls of jejunum and ileum were 3.7 to 3.9 mm thick, with decreased echogenicity compared to the liver. The descending colon was located on the left side of the abdominal cavity with a similar echogenicity as the small intestine. The kidneys were located below the costal border, presented multilobulated morphology with the cortex of similar echogenicity to the liver parenchyma surrounding the medulla that was anechoic.